Replantation in scapulothoracic avulsion amputation of the right upper limb in a 3-year-old child- A preliminary report - Sanjay Mahendru; Rakesh Kumar Khazanchi; Vimalendu Brajesh; Akram Jawed; Aditya Aggarwal; Hardeep Singh; Sukhdeep Singh; S. Krishnan (Indian Journal of Plastic Surgery)
Replantations for major amputations of upper extremity have been widely performed. We report a unique case of successful replantation of scapulothoracic avulsion amputation in a child. In this manuscript, we discuss the various challenges faced during the procedure and chances of neural recovery.